REVIEW: Media hypocrisy - Robie, David (Pacific Journalism Review : Te Koakoa, 1994)
Review of A Critical View of Western Journalism and Scholarship on East Timor, by Geoffrey Gunn, Manila: Journal of Contemporary Asia Publishers, 1994. 272 pp. K10.
Shortly after the Dili massacre in November 1991, I was paid a 'kill' fee by one of New Zealand's largest dailies rather than publish a detailed account of the circumstances leading up to the massacre and an exposure of the Indonesian lies and distortions. The full-page broadsheet article had already been set up in type and laid out when it was 'pulled' from the paper. A New Zealander was among those who were brutally murdered by Indonesian troops that tragic day.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYxaTEuNTI3